A functional variant in the 3′-UTR of angiopoietin-1 might reduce stroke risk by interfering with the binding efficiency of microRNA 211 - Chen, Jingzhou; Yang, Tao; Yu, Hui; Sun, Kai; Shi, Yi; Song, Weihua; Bai, Yongyi; Wang, Xiaojian; Lou, Kejia; Song, Yan; Zhang, Yinhui; Hui, Rutai (Human molecular genetics, 2010)
Angiopoietin-1 is a vascular strengthening factor during vascular development and a protective factor for pathological vascular inflammation and leakage. Brain vascular leaking and inflammation are two important pathological processes of stroke; therefore, we hypothesized that variants of the microRNA-binding site in angiopoietin-1 would affect its expression and confer a risk of stroke. To test our hypothesis, a predicted microRNA-binding site was found in the 3′-UTR of angiopoietin-1 using bioinformatics; variant rs2507800 was identified to be located in the miR-211-binding site of angiopoietin-1. Secondly, the effects of the identified variant on angiopoietin-1 translation were assessed using a luciferase reporter assay and ELISA. We found that the A allele of rs2507800 suppressed angiopoietin-1 translation by facilitating miR-211 binding, but not the T allele. Subjects carrying the TT genotype had higher plasma angiopoietin-1 levels than those with the A allele. Finally, the association of the variant with stroke was tested in 438 stroke patients and 890 controls, and replicated in an independent population of 1791 stroke patients and 1843 controls. The TT genotype resulted in a significant reduction in overall stroke risk {OR, 0.51 [95% confidence interval (CI), 0.36–0.74], P = 0.0003}, ischemic stroke [OR, 0.56 (95% CI, 0.36–0.85), P = 0.007] and hemorrhagic stroke [OR, 0.46 (95% CI, 0.26–0.80), P = 0.007]. These results were confirmed in an independent study. Our results provide evidence that the TT genotype (rs2507800) in the 3′-UTR of angiopoietin-1 might reduce the risk of stroke by interfering with miR-211 binding.